Analisa Laporan Keuangan untuk Menilai Kinerja Keuangan CV. D’printing - Aida Anjelina; Hartono Hartono; Toto Heru Dwihandoko (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2024)
This study aims to evaluate the financial performance of CV. D'Printing by analyzing liquidity, solvency, profitability, and activity ratios. The research is quantitative with a descriptive approach. The data analyzed comprises the financial statements of CV. D'Printing for the 2019-2023 period. The analysis techniques used are quantitative analysis and time series analysis, comparing financial ratios from one period to another. The results indicate that the company's liquidity and solvency ratios are in good and healthy condition. However, the activity ratios show suboptimal performance, with a decline in percentages each year. Overall, CV. D'Printing has a solid financial performance, although some areas need improvement..